2021
DOI: 10.1186/s13019-021-01561-4
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen-year experience with pericardiectomy at a tertiary referral center

Abstract: Purpose Pericardiectomy has traditionally carried relatively high perioperative mortality and morbidity, with few published reports of intermediate- and long- term outcomes. We investigated our 15-year experience performing pericardiectomy at our institution. Methods Retrospective study of all patients who underwent pericardiectomy at our institution between 2005 and 2019. Baseline demographics, intraoperative details, and postoperative outcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
1
6
0
1
Order By: Relevance
“…Regarding the relationship between mortality and CP etiologies, we observed that RDT CP has the worst prognosis, since in our case it corresponds to 50% of the deaths; this association also coincides with that reported in the literature [ 1 , 8 , 13 ] . On the other hand, IDP CP has the best prognosis [ 4 , 12 ] .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the relationship between mortality and CP etiologies, we observed that RDT CP has the worst prognosis, since in our case it corresponds to 50% of the deaths; this association also coincides with that reported in the literature [ 1 , 8 , 13 ] . On the other hand, IDP CP has the best prognosis [ 4 , 12 ] .…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, RDT CP is a less prevalent etiology in most series but with high morbimortality, which we were also able to prove since 50% of our mortality was due to this etiology. Several authors describe radiation as a poor prognostic factor in the development of CP and its subsequent surgical resection [ 1 , 7 , 8 , 13 ] . Bertog et al [ 8 ] describe an average of 11 years (range between 2-20 years) between exposure to radiation and pericardiectomy, in our case it was 18.5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, radical pericardiectomy is preferred. [91][92][93] While pericardiectomy has been considered a high-risk operation with operative mortality of 6% to 10%, [94][95][96] recent reports from specialty centers suggest operative risk is largely dependent on etiology and comorbidities, with operative mortality for idiopathic cases less than 1.5%. 90,97,98…”
Section: Surgerymentioning
confidence: 99%
“…Echocardiography is the first-line imaging modality for the diagnosis and invasive hemodynamic measurements are reserved for ambiguous cases [ 3 ]. Pericardiectomy remains the definitive treatment for CP, however, a trial of anti-inflammatory medications is preferred initially [ 4 ]. We present a case of inadequately treated acute pericarditis resulting in constriction necessitating pericardiectomy.…”
Section: Introductionmentioning
confidence: 99%